Sentinel Lymph Node Biopsy in Prostate Cancer Using the SENSEI® Drop-In Gamma Probe. (January 2022) - Abascal Junquera, Jose Maria; Mestre-Fusco, Antoni; Grootendorst, Maarten Ruben; Vidal-Sicart, Sergi; Fumado, Lluis
Abstract : Abstract: Minimally invasive surgery in the form of laparoscopic and robot-assisted procedures has been widely adopted in the field of prostate cancer. When performing minimally invasive radioguided surgery, conventional rigid laparoscopic gamma probes have limited maneuverability and control due to their form factor, which may hinder detection of radiotracer-avid lesions in anatomically challenging areas. A drop-in gamma probe has been developed to address these limitations. Our group report on the first clinical use of this probe (SENSEI ® ) as part of an ongoing prospective, international, multicenter clinical trial in primary prostate cancer patients undergoing 99m Tc-nanocolloid sentinel lymph node biopsy.